Case report: Resuscitative endovascular balloon occlusion after iatrogenic injury of the common iliac artery during neurosurgical dorsal lumbar microdiscectomy - Fiedler-Kalenka, Mascha; Böckler, Dittmar; Giese, Henrik; Popp, Erik; Schmitt, Felix; Weigand, Markus A.; Erhart, Philipp (Frontiers in medicine, 2023)
Introduction and importanceThis case report describes resuscitative endovascular balloon occlusion (REBOA) of the aorta in a patient with life-threatening iatrogenic bleeding of the right common iliac artery during elective dorsal lumbar spine surgery. REBOA is an emergency procedure for temporary intra-aortic balloon occlusion being increasingly reported and published since its inauguration in 1954. The interdisciplinary management of hemorrhage and technical notes for a successful REBOA procedure will be presented.Case presentationA 53-year-old female patient was admitted to the neurosurgery clinic suffering from left-sided L5 radiculopathy. During surgery, the anterior longitudinal ligament was perforated and an arterial vessel was lacerated. The patient became hemodynamically unstable demanding prompt supine repositioning and cardiopulmonary resuscitation (CPR). REBOA enabled cardiovascular stabilization after 90 min of CPR and laparotomy with vascular reconstruction and contributed to the survival of the patient without major clinical deficits. The patient was discharged from the ICU after 7 days.Clinical discussionResuscitative endovascular balloon occlusion of the aorta is an emergency procedure to control life-threatening hemorrhage. REBOA should be available on-scene and applied by well-trained vascular surgery personnel to control vascular complications or extend to emergency laparotomy and thoracotomy with aortic cross-clamping in case of in-hospital non-controllable hemorrhages. In case of ongoing CPR, we recommend surgical groin incision, open puncture of the pulseless common femoral artery, and aortic balloon inflation in REBOA zone I. Hereby, fast access and CPR optimization for heart and brain perfusion are maintained.ConclusionTraining for REBOA is the decisive factor to control selected cases of in-house and outpatient massive arterial abdominal bleeding complications.
Gesehen am 16.03.2023